Organizing Skills For Zakat Utilisation Dynamics In Faith-Based Organization - Machdum, Sari Viciawati (Universitas Negeri Semarang, 2018)
This article discusses the implementation of the microfinance program in one of the zakat institutions in Indonesia, Pos Keadilan Peduli Umat (PKPU) as Faith-Based Organization (FBO). Utilization of zakat through microfinance requires the community workers to be able to be adaptive to the dynamics of the existing system within himself, organization, community and the organization environment. The dynamic of the social system in the process of microfinance will provide its challenges, both for change agents and service recipients. Based on a qualitative approach, this study describes the organizing skills that Community workers needed to have in implementing microfinance program. The data were collected through in-depth interviews, participant observation, and literature study. This study illustrates organizing skills –that could help community workers to be more adaptive to organizational and environmental dynamics in the process of microfinance– are organizational restructuring based on environmental needs and changes, flexible direction to develop a supportive organizational climate, and the development of organizing skills down to the grassroots.